2014
DOI: 10.1177/1545968314547766
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Tools to Measure Improvements in Upper-Limb Function With Poststroke Therapy

Abstract: These results suggest that no single test is suitable for measuring function and improvement across the spectrum of poststroke upper-limb dysfunction and that assessment tool selection should be based on the level of residual motor-function of individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 50 publications
1
37
0
2
Order By: Relevance
“…However the Fugl-Meyer Scale was constructed on the assumptions that recovery proceeds in a proximal-to-distal fashion and from synergistic-to-isolated movements (Fugl-Meyer, Jaasko et al 1975; Gladstone, Danells et al 2002); however, both these assumptions have been contested recently (Woodbury, Velozo et al 2007; Beebe and Lang 2008; Crow and Harmeling-van der Wel 2008). Furthermore, the Fugl-Meyer scale may show ceiling effects for fine motor skills in higher functioning patients (Thompson-Butel, Lin et al 2014). …”
Section: Clinical Outcomesmentioning
confidence: 99%
“…However the Fugl-Meyer Scale was constructed on the assumptions that recovery proceeds in a proximal-to-distal fashion and from synergistic-to-isolated movements (Fugl-Meyer, Jaasko et al 1975; Gladstone, Danells et al 2002); however, both these assumptions have been contested recently (Woodbury, Velozo et al 2007; Beebe and Lang 2008; Crow and Harmeling-van der Wel 2008). Furthermore, the Fugl-Meyer scale may show ceiling effects for fine motor skills in higher functioning patients (Thompson-Butel, Lin et al 2014). …”
Section: Clinical Outcomesmentioning
confidence: 99%
“…This analysis was designed to minimise the floor and/or ceiling effects of individual assessments, given the heterogeneous distribution of motor-function within this cohort (ThompsonButel et al, 2014;2015). The first principle component was extracted to generate a PCA motorfunction score for each patient, whereby lower scores correspond to lower motor-function.…”
Section: Motor Functional Assessment Analysismentioning
confidence: 99%
“…8 To determine the optimal method to evaluate post-stroke impairment, recent studies have compared assessment tools, including the use of the FM-UE. 911 …”
mentioning
confidence: 99%
“…10,11,16 For example, to avoid ceiling effects common to the FM-UE, it has been suggested that the test should be used for measuring baseline and changes in impairment only among patients with lower motor function. 10,11,17 Furthermore, the utility of the FM-UE used alone to assess function has been questioned. Thompson-Butel and colleagues hold that a single instrument is not able to distinguish levels of post stroke impairment.…”
mentioning
confidence: 99%